Granulomas and Inflammation: Host-Directed Therapies for Tuberculosis - Ndlovu, Hlumani; Marakalala, Mohlopheni J. (Frontiers in Immunology, 2016)
Tuberculosis remains a leading global health problem that is aggravated by emergence of drug-resistant strains, which account for increasing number of treatment-refractory cases. Thus, eradication of this disease will strongly require better therapeutic strategies. Identification of host factors promoting disease progression may accelerate discovery of adjunct host-directed therapies (HDTs) that will boost current treatment protocols. HDTs focus on potentiating key components of host anti-mycobacterial effector mechanisms, and limiting inflammation and pathological damage in the lung. Granulomas represent a pathological hallmark of TB. They are comprised of impressive arrangement of immune cells that serve to contain the invading pathogen. However, granulomas can also undergo changes, developing caseums and cavities that facilitate bacterial spread and disease progression. Here we review current concepts on the role of granulomas in pathogenesis and protective immunity against TB, drawing from recent clinical studies in humans and animal models. We also discuss therapeutic potential of inflammatory pathways that drive granuloma progression, with a focus on new and existing drugs that will likely improve TB treatment outcomes.